Cardiovascular death risk in mid-range ejection fraction heart failure: insights from cardiopulmonary exercise test. (14th October 2021) - Gallo, G; Piepoli, M; Corra', U; Salvioni, E; Perrone Filardi, P; Metra, M; Limongelli, G; Senni, M; Parati, G; Cicoira, M.A; Sciomer, S; Sinagra, G; et al.
Abstract: Background: The pivotal role of cardiopulmonary exercise testing (CPET) in the assessment of functional capacity and prognosis of patients with heart failure with reduced ejection fraction (HFrEF), either as a single CPET parameter (i.e. peak oxygen uptake, peak VO2), as a combination of CPET parameters (i.e. oxygen uptake at the anaerobic threshold (AT) and ventilatory efficiency (VE/VCO2 slope), or as a part of more comprehensive scores (i.e. Metabolic Exercise combined with Cardiac and Kidney Indexes, MECKI) is well established. Just few studies are available with respect a possible role of CPET in risk stratification of patients in HF with midrange EF (HFmrEF) subset, namely HF patients with LVEF between 40% and 49%. Purpose: The aim of the present large Italian multicenter study was to characterize and to compare stable HFmrEF and HFrEF patients in terms of exercise capacity as well as of instrumental and laboratory variables. We analyzed a possible independent and incremental prognostic value of CPET parameters in identifying those HFmrEF patients at high cardiovascular death risk. Methods: We retrospectively analyzed clinical and CPET data of stable HF patients with HFrEF and HFmrEF from the MECKI Score database. Five-thousand-seven-hundred-eleven patients, 4, 535 with HFrEF and 1, 176 with HFmrEF, were considered for the study. The end-point was cardiovascular death at 5 years. The median follow-up was 1343 days (25th–75th range, 627–2403 days). Results: Cardiovascular death occurred in 552 HFrEF (12.2% event rate) and 61 HFmrEF (5.2% event rate) patients. At multivariate analysis, an independent role of variables included in the MECKI score (age, atrial fibrillation, LVEF, haemoglobin, sodium, MDRD, AT identification, VO2 at AT, peak VO2 also expressed as percentage of the maximum predicted, VE/VCO2 slope) was confirmed in HFrEF group (C-index=0.744) whereas, in the HFmrEF group, only age and peak VO2 remained outcome predictors (C-index=0.745). We identified a peak VO2 <55% of predicted and a VE/VCO2 slope >31 as the most accurate cut-off values able to identify a HFmrEF subgroup with a cardiovascular mortality rate significantly higher than the overall HFmrEF (5.2% vs 8.5%) (Figure 1). By using both cut-off values contextually, we recognized a relatively small HFmrEF population with a cardiovascular risk quite similar to the HFrEF sample (11.4% vs 12.2%) (Figure 1). Conclusions: Present data support the CPET as a useful tool in the HFmrEF management. Besides the peak VO2, which resulted as a strong independent outcome predictor, also a number of other CPET variables were associated to the cardiovascular death risk. Particularly, a peak VO2 ≤55% of the maximum and a VE/VCO2 slope ≥31 identified a HFmrEF subgroup of patients with a high cardiovascular death risk, similar to the one observed in the HFrEF group. Funding Acknowledgement: Type of funding sources: None.